PENGARUH MEDIA DIORAMA TERHADAP HASIL BELAJAR IPAS PADA MATERI KERAGAMAN BUDAYA - Muna, Sabilatul; Puspitasari, Nimas; Wijayanti, Atrianing Yessi (Universitas Tanjungpura, 2025)
This study looks into how visual media affects how well fourth graders do in IPAS classes, particularly about the matter of cultural diversity at MI Karangduren. The study was started because students weren't doing well, which is thought to be because they didn't have enough hands-on and interactive learning tools. with a quantitative approach that uses a quasiexperimental design with a control group that is different from the experimental group. The study comprised 52 people. They were divided into two factions: the experimental group learned with diorama media, and the control group learned with regular teaching materials. A multiple-choice test with 30 validated questions was used to get the data. The research showed a clear difference in the results of the posttest, with the experimental group doing better. The t-test showed that the calculated t-value (3.0679) was higher than the crucial value (2.021), which means that diorama media had a big effect on how well students learned. These results show that using dioramas as a teaching technique in IPAS education could be useful. Future research should look into how well it works for different subjects and levels of schooling.